2023
DOI: 10.1038/s41392-023-01376-w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of obesity- and diabetes mellitus-related pancreatic carcinogenesis: a comprehensive and systematic review

Abstract: Research on obesity- and diabetes mellitus (DM)-related carcinogenesis has expanded exponentially since these two diseases were recognized as important risk factors for cancers. The growing interest in this area is prominently actuated by the increasing obesity and DM prevalence, which is partially responsible for the slight but constant increase in pancreatic cancer (PC) occurrence. PC is a highly lethal malignancy characterized by its insidious symptoms, delayed diagnosis, and devastating prognosis. The intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 547 publications
(871 reference statements)
0
6
0
1
Order By: Relevance
“…This may impair acinar enzyme production and islet hormone secretion, providing a histopathological basis for clinical reports of statininduced pancreatitis and diabetes. 10 Notably, the patterns observed here evoke the initial changes in type 1 diabetes pathogenesis. Lymphocytic infiltration and lipomatosis mark the early stages, followed by progressive islet destruction.…”
Section: Discussionmentioning
confidence: 55%
“…This may impair acinar enzyme production and islet hormone secretion, providing a histopathological basis for clinical reports of statininduced pancreatitis and diabetes. 10 Notably, the patterns observed here evoke the initial changes in type 1 diabetes pathogenesis. Lymphocytic infiltration and lipomatosis mark the early stages, followed by progressive islet destruction.…”
Section: Discussionmentioning
confidence: 55%
“…These effects are primarily exerted through regulating the structure and function of cell membranes, cellular homeostasis, and hormone synthesis. 47 , 48 , 49 Therefore, with reference to the optimization of TyG‐neck circumference (TyG‐NC), TyG‐neck circumference to height ratio (TyG‐NHtR), TyG‐waist circumference (TyG‐WC), TyG‐waist to height ratio (TyG‐WHtR), TyG‐body mass index (TyG‐BMI), 22 we optimized TyG‐BMI, and the product of TyG‐BMI and TC/HDL‐c was used as the GLMI. The level of IR in PC patients with diabetes was evaluated using GLMI.…”
Section: Discussionmentioning
confidence: 99%
“…Although etiopathogenetic mechanisms that would explain the link between a high BMI and pancreatic cancer were not fully understood, some authors suggested that pancreatic fatty infiltration, chronic inflammation, altered cellular metabolism, hormone dysregulation, microbial dysbiosis, or immune cell infiltration may be involved in pancreatic carcinogenesis [29,30]. It is known that obesity favors the release of pro-inflammatory cytokines such as tumor necrosis factor α and Interleukin-6, which are linked to the development of inflammation, and the onset of cancer [31]. Also, one study found that fatty acid-binding protein 4 (that induces inflammation to promote cancer cell migration, invasion, and metastasis under obese conditions) was overexpressed in the serum of patients with obesity and was associated with poor overall survival in pancreatic cancer [32].…”
Section: Discussionmentioning
confidence: 99%